The role of MRI and CT of the brain in first episodes of psychosis and behavioural abnormality. Issue 9 (September 2021) - Kular, S.; Griffin, K.; Batty, R.; Hoggard, N.; Connolly, D.
Abstract : AIM: To investigate whether computed tomography (CT)/magnetic resonance imaging (MRI) brain imaging is associated with detection of structural causes of a first episode of psychosis (FEP) or first episode of behavioural abnormality (FEB) in the paediatric population, as this has not been previously documented in the literature. MATERIALS AND METHODS: Individuals with FEP/FEB but no neurological signs referred to a tertiary children's centre for cerebral MRI or CT were reviewed retrospectively. Individuals were evaluated independently with one technique (CT or MRI) only. RESULTS: Thirty-four consecutive cerebral MRI and six consecutive CT examinations were identified between 2017 and 2020. No patients were identified as having an organic cause for the psychosis at MRI or CT. Four patients (9%) had incidental findings on MRI, unrelated to the psychosis, such as prominent perivascular spaces, hypoplastic transverse sinus, and sinonasal mucosal wall thickening. No abnormal findings were seen on CT. There was therefore no obvious difference between MRI and CT imaging in detecting organic disease potentially responsible for FEP. CONCLUSION: Routine structural MRI or CT of the brain is unlikely to reveal disease leading to a significant change in management. MRI demonstrated only a few incidental findings, unrelated to the child's clinical history. Therefore, routine brain structural imaging of FEP/FEB in paediatric patients without focal neurology may not be routinely required. If imaging is requested, then there is no significant difference between CT and MRI in detecting clinically significant lesions. Highlights: First episodes of behavioural abnormality or psychosis often cause clinical dilemma. Imaging can often be seen as a route for excluding underlying organic pathology. In almost all cases CT or MRI scanning does not show any underlying pathology. Imaging may therefore not be indicated as a routine investigation for FEP/FEB.